2014
DOI: 10.3389/fnhum.2014.00855
|View full text |Cite
|
Sign up to set email alerts
|

A temporal window for estimating surface brightness in the Craik-O'Brien-Cornsweet effect

Abstract: The central edge of an opposing pair of luminance gradients (COC edge) makes adjoining regions with identical luminance appear to be different. This brightness illusion, called the Craik-O'Brien-Cornsweet effect (COCe), can be explained by low-level spatial filtering mechanisms (Dakin and Bex, 2003). Also, the COCe is greatly reduced when the stimulus lacks a frame element surrounding the COC edge (Purves et al., 1999). This indicates that the COCe can be modulated by extra contextual cues that are related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Adjacent objects are perceived as having different brightness based on variations in staining intensity, when in fact they are the same (Figure 1, D). [24][25][26] This illusion may influence a pathologist's assessment of the staining of adjacent cells, where staining must be assessed for both the cytoplasm (middle) and membrane (edge); dissimilarities of staining intensity at the membrane may lead to misinterpretation of cytoplasmic staining intensity.…”
Section: Visual Traps As Sources Of Biasmentioning
confidence: 99%
“…Adjacent objects are perceived as having different brightness based on variations in staining intensity, when in fact they are the same (Figure 1, D). [24][25][26] This illusion may influence a pathologist's assessment of the staining of adjacent cells, where staining must be assessed for both the cytoplasm (middle) and membrane (edge); dissimilarities of staining intensity at the membrane may lead to misinterpretation of cytoplasmic staining intensity.…”
Section: Visual Traps As Sources Of Biasmentioning
confidence: 99%
“…In this illusion, the brightness change along the edge in the middle influences the perception of both surfaces to the left and right of the middle having different brightness when in fact the majority is of the same brightness. To confirm, cover the middle of the image to see that the majority of the area is the same intensity or shade of gray (Kurki et al 2009; Purves, Shimpi, and Lotto 1999; Masuda et al 2014; Aeffner et al 2017). Herman grid illusion (H) is a display of lateral inhibition (LI), which is a perceived increase of contrast and sharpness (Aaen-Stockdale 2007).…”
Section: Flexing Your Muscle: Techniques To Strengthen Muscle Biomarker Assessmentmentioning
confidence: 99%
“…The Craik-O'Brien-Cornsweet illusion demonstrates the human's perception of surfaces based on the optical characteristics of their edges (Fibonacci, 2007; Figure 4G). Adjacent objects appear to have a different brightness caused by a variation in staining intensity at the interface only, when in fact these adjacent objects are of the same staining intensity for the majority of the surface (Kurki et al , 2009, Purves, Shimpi and Lotto, 1999, Masuda et al , 2014). This effect is likely at play when it has been reported that the same membranous staining intensity is perceived as being different, depending upon if it is evaluated next to cytoplasm with staining or devoid of staining (Conway et al , 2008).…”
Section: Introductionmentioning
confidence: 99%